2001
DOI: 10.1074/jbc.m101394200
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-dependent Cleavage of ErbB-2 by Geldanamycin and Staurosporin

Abstract: The geldanamycin-induced degradation of ErbB-2 produces a 23-kDa carboxyl-terminal fragment, which has been isolated and subjected to amino-terminal microsequencing. The obtained sequence indicates that the amino terminus of this fragment corresponds to Gly-1126 of ErbB-2. Analysis of the residues immediately before Gly-1126 suggests that cleavage may involve caspase activity. Site-directed mutagenesis of Asp-1125 in ErbB-2 prevents geldanamycin-provoked formation of the 23-kDa fragment, consistent with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 47 publications
4
38
1
Order By: Relevance
“…For certain substrates removal of a regulatory domain results in their constitutive activation, as in the case of various kinases (11,12). For others, cleavage results in a loss of function, and the resulting fragments are frequently degraded by the 26S proteasome (5)(6)(7)(8)(9)(10). In this study, we found an interaction between caspases and the ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…For certain substrates removal of a regulatory domain results in their constitutive activation, as in the case of various kinases (11,12). For others, cleavage results in a loss of function, and the resulting fragments are frequently degraded by the 26S proteasome (5)(6)(7)(8)(9)(10). In this study, we found an interaction between caspases and the ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 52%
“…Caspase cleavage can inactivate proteins or generate dominant-negative inhibitors, as in the case of gelsolin, RIP1, and eIF4E-BP1 (4). Moreover, caspase cleavage of numerous substrates, including IRF-3, ErbB2, cyclin E, claspin, SSRP1, and Twist, can enhance their turnover by the proteasome (5)(6)(7)(8)(9)(10). Conversely, caspases can also constitutively activate proteins, particularly kinases such as PKC and Mst1 (11,12), or change the function of a protein altogether, as seen in the conversion of antiapoptotic BCL-2 proteins into proapoptotic BAX-like proteins (13).…”
mentioning
confidence: 99%
“…HSP90 inhibition also induces cleavage of the cytoplasmic part of ErbB2, resulting in a transmembrane 135-kDa ErbB2 and short-lived cytoplasmic fragments (Tikhomirov and Carpenter, 2000;Lerdrup et al, 2006). The cleavage occurs in the kinase domain and a similar cleavage is seen after stimulation with curcumin or staurosporine (Tikhomirov and Carpenter, 2001) or in cells with high levels of ␣6␤1 integrin (Shimizu et al, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…HSP90 inhibition also induces cleavage of the cytoplasmic part of ErbB2, resulting in a transmembrane 135-kDa ErbB2 and short-lived cytoplasmic fragments (Tikhomirov and Carpenter, 2000;Lerdrup et al, 2006). The cleavage occurs in the kinase domain and a similar cleavage is seen after stimulation with curcumin or staurosporine (Tikhomirov and Carpenter, 2001) or in cells with high levels of ␣6␤1 integrin (Shimizu et al, 2003).It has remained elusive whether endocytosis and C-terminal cleavage of ErbB2 are independent or correlated events. If positively correlated, C-terminal cleavage of ErbB2 could promote endocytosis by releasing ErbB2 from a retention mechanism that normally sequesters the receptor at the plasma membrane (Sorkin et al, 1993;Hommelgaard et al, 2004;Lerdrup et al, 2006) or by exposure of an unknown cryptic motif stimulating endocytosis.…”
mentioning
confidence: 99%
“…In the case of several RTKs (ErbB-2 [Tikhomirov and Carpenter 2001;Benoit et al 2004;Strohecker et al 2008], Ret [Bordeaux et al 2000;Cabrera et al 2011], ALK [Mourali et al 2006;Racaud-Sultan et al 2006], TrkC [Tauszig- Delamasure et al 2007], and Met [Tulasne et al 2004;Pozner-Moulis et al 2006;Foveau et al 2007;Deheuninck et al 2009]) there is evidence that caspase activity cleaves the cytoplasmic domain to produce an ICD fragment. Because the fragment is often produced by two cleavage events within the cytoplasmic domain, the fragment is often considerably smaller than that produced by intramembrane proteolysis.…”
Section: Nonsecretase Formation Of Rtk Icd Fragments Caspase-dependenmentioning
confidence: 99%